Impact of depressive symptoms on oxidative stress in patients with psoriasis. (March 2013) - Karababa, Fatih; Yesilova, Yavuz; Turan, Enver; Selek, Salih; Altun, Hacer; Selek, Sahabettin
Abstract : Background: Depression and anxiety disorders often accompany psoriasis. Increased reactive oxygen radicals and impaired antioxidant systems are considered to play a role both in psoriasis and depression and anxiety disorders. Accordingly, in this study, we aimed to investigate the effects of depressive and anxiety symptoms on oxidative stress in patients with psoriasis. Materials and methods: Hospital Anxiety and Depression Scale( HADS) forms were completed by 39 psoriasis patients and 25 volunteer controls. Serum total antioxidant capacity (TAC) and total oxidant capacity (TOC) parameters were analysed in serum samples, after which oxidative stress index (OSI) was calculated in whole study population. Laboratory data were analysed with a Kruskal–Wallis test to determine the severity of HADS and the presence of psoriasis among four groups. Results: The psoriasis patients had higher HADS scores, higher OSI and TOC levels, and lower TAC levels compared with the control group. Comparison among four groups with/without psoriasis and higher/lower HADS scores revealed statistically significant differences with regard to TAC (Kruskal–Wallis P = 0.0047) and TOC (Kruskal–Wallis P < 0.001) levels and OSI (Kruskal–Wallis P < 0.001); the difference was mainly based on the difference between cases with and without psoriasis and on HADS scores in control subjects ( P < 0.05 for post hoc comparisons). TAC, TOC, and OSI levels did not differ significantly in psoriasis patients with regard to higher or lower HADS scores. Conclusion: Based on the findings of this study, the presence of either psoriasis or higher HADS scores in the control subjects was associated with increased oxidative stress, whereas presence of higher HADS scores did not lead to further increase in oxidative stress in psoriatic patients.